Givinostat for the treatment of polycythemia vera. (August 2014) - Pieri, Lisa; Guglielmelli, Paola; Finazzi, Guido; Vannucchi, Alessandro M
<x xml:space="preserve">Abstract</x> Introduction: Polycythemia vera (PV) is a myeloproliferative neoplasm for which no curative treatment currently exists. However, the discovery of abnormally activated JAK/STAT signaling pushed the clinical development of JAK1/JAK2 inhibitors and other target drugs, including inhibitors of histone deacetylases (HDACi). Areas covered: We reviewed preclinical studies and clinical trials with <ext-link ext-link-type="uri" xlink:href="http://informahealthcare.com/action/doSearch?type=advanced&displaySummary=true&displaySummary=true&field1=keywords&text1=Givinostat&logicalOpe1=OR&field2=articletitle&text2=Givinostat&logicalOpe2=AND&field3=all&text3=&search=Search&categoryId=41010274&categoryId=40002416&categoryId=40004717&categoryId=40004717&filter=multiple&AfterMonth=1&AfterYear=&BeforeMonth=12&BeforeYear=&sortBy=date&nh=20" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink">givinostat, a Class I and II HDACi, through PubMed research and communications to the meeting of the most important hematology associations. Expert opinion: Proof of evidence has been obtained with givinostat earlier in JAK2V617F mutated cells and then in two clinical trials in patients with PV. Treatment resulted effective in inducing hematological response, symptomatic improvement and reduction of enlarged spleen, with good tolerability. Further clinical development is required to more clearly define the role of Givinostat in the therapeutic armamentarium of PV and exploit the full activity of the drug against the myeloproliferative clone.